Structural model of a voltage-gated potassium channel based on spectroscopic data. (August 2001) - Haris, P. I.
Abstract : It is estimated that membrane proteins comprise as much as 30% of most genomes. Yet our knowledge of membrane-protein folding is still in its infancy. Consequently, there is a great need for developing approaches that can further advance our understanding of how peptides and proteins interact with membranes and thereby attain their folded structure. An approach that we have been exploring involves dissecting voltage-gated ion channels into simple peptide domains for the purpose of determining their structure in different media using physical techniques. We have synthesized peptides corresponding to the six membrane-spanning segments, as well as the pore domain, of the Shaker channel and characterized their secondary structures. From these studies we have developed a model for the transmembrane structure of the Shaker potassium channel that is constructed from α-helices. The hard structural data obtained from these studies lends support to the recent theoretical models of this channel protein that have been developed by others.